Biochar amendment increases bacterial diversity and vegetation cover in trace element-polluted soils: A long-term field experiment. (November 2020) - Campos, Paloma; Miller, Ana Z.; Prats, Sergio A.; Knicker, Heike; Hagemann, Nikolas; De la Rosa, José M.
Abstract: Application of biochar has been widely suggested as a remediation tool for trace element-polluted soils, but the impact of biochar on microbial communities and on native plants remain largely unknown. To overcome this knowledge gap, biochar produced from rice husk and olive pit were applied at a rate of 8 t ha −1 into a soil with two contrasting levels of trace elements (high and moderate) to study their effects on soil microbial community composition, vegetation cover and soil properties after 1, 6, 12 and 20 months under field conditions. Differences in bacterial community composition were studied using the Illumina Miseq technology of the 16S rRNA gene. Although variations in soil properties and ecological function were seasonal and soil-type dependent, biochar application enhanced soil properties and vegetation cover in the moderately polluted soil (MPS), and increased microbial diversity as well as vegetation cover in the highly polluted soil (HPS). Enzymatic activities and soil respiration rates were not modified with the application of biochar, but increased total carbon content of soils. The application of biochar from crop residues to trace-element contaminated soils provided environmental benefits, including plant diversity and growth, as well as the increase of bacterial diversity and carbon sequestration. Highlights: Biochar was applied in moderately and highly polluted soils under field conditions. Biochar application increased bacterial and plant diversity in highly polluted soil. Bacterial diversity slightly changed in moderately polluted soil with biochar. Soil pH was key factor of bacterial community structure. Seasonal changes affected microbial community, soil respiration and vegetation.